Slope reinforcement analysis using retaining structures: a case study in a heritage temple area in Yogyakarta - Amalina, Anisa Nur; Jananto, Bayu Tri (Journal of Engineering and Applied Technology, 2026)
Indonesia is home to numerous cultural heritage sites situated on sloping terrain, where geotechnical stability plays a crucial role in preservation and restoration efforts. One such site is a Buddhist stupa in Sambirejo, Prambanan, Sleman, located approximately 200 meters north of Barong Temple. The stupa lies on a slope with a 16.10% gradient underlain by lithosol and regosol soils of limited thickness, which raises potential risks of instability. This study aims to evaluate the slope stability conditions of the temple area and to propose suitable reinforcement designs to ensure structural safety. Field investigations, including cone penetration tests (CPT) and hand boring, revealed that the subsurface consists primarily of fine to medium-silty sand with a groundwater table at a depth of 2.5 m. Stability analyses were performed using both manual calculations based on SNI 8460:2017 and numerical modelling with PLAXIS. Two reinforcement alternatives were assessed: cantilever retaining walls and concrete sheet piles under static and pseudo-static (seismic) conditions. The results showed that the safety factor increased by 17.9% and 12.5% for cantilever and sheet pile walls, respectively, under static loading, and by approximately 8% under dynamic conditions. These findings confirmed that both methods effectively enhance slope stability, with cantilever retaining walls demonstrating better performance in minimizing deformation than concrete sheet pile.